2007
DOI: 10.1086/519949
|View full text |Cite
|
Sign up to set email alerts
|

SN 2006gy: Discovery of the Most Luminous Supernova Ever Recorded, Powered by the Death of an Extremely Massive Star like η Carinae

Abstract: We report the discovery and early observations of the peculiar Type IIn supernova (SN) 2006gy in NGC 1260. With a peak visual magnitude of about À22, it is the most luminous supernova ever recorded. Its very slow rise to maximum took $70 days, and it stayed brighter than À21 mag for about 100 days. It is not yet clear what powers the enormous luminosity and the total radiated energy of $10 51 erg, but we argue that any known mechanism-thermal emission, circumstellar interaction, or 56 Ni decay-requires a very… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
521
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 519 publications
(540 citation statements)
references
References 82 publications
16
521
1
2
Order By: Relevance
“…In contrast, SLSNe-II have been attributed to more luminous versions of Type IIn supernova, which themselves are believed to be due to the end stages of luminous blue variables (LBVs) with massive circumstellar matter (CSM) envelopes. Both types of SLSNe have been measured to emit more than 10 51 erg of energy (Smith et al 2007;Drake et al 2010;Quimby et al 2011;Rest et al 2011) and are thus within the range of almost all the flares shown here. Furthermore, examples of SLSNe have been discovered up to redshifts of z = 3.9 (Cooke et al 2012).…”
Section: Superluminous Supernovaesupporting
confidence: 60%
“…In contrast, SLSNe-II have been attributed to more luminous versions of Type IIn supernova, which themselves are believed to be due to the end stages of luminous blue variables (LBVs) with massive circumstellar matter (CSM) envelopes. Both types of SLSNe have been measured to emit more than 10 51 erg of energy (Smith et al 2007;Drake et al 2010;Quimby et al 2011;Rest et al 2011) and are thus within the range of almost all the flares shown here. Furthermore, examples of SLSNe have been discovered up to redshifts of z = 3.9 (Cooke et al 2012).…”
Section: Superluminous Supernovaesupporting
confidence: 60%
“…SLSNII show conspicuous signatures of hydrogen; however, the hydrogen feature is so far like that of SNIIn (Dessart et al 2015a), i.e., narrow emission signatures of hydrogen, e.g., SN2006gy (Smith et al 2007) and 2008am (Chatzopoulos et al 2011).…”
Section: Super-luminous Supernovaementioning
confidence: 97%
“…Some SLSNe clearly bear the sign of interaction with a hydrogen-rich circum-stellar medium (CSM; Smith et al 2007;Ofek et al 2007;Drake et al 2011;Benetti et al 2014). This masks the actual SN ejecta, making their nature unclear, although a link with massive stars is likely (e.g., Smith et al 2007;Agnoletto et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This masks the actual SN ejecta, making their nature unclear, although a link with massive stars is likely (e.g., Smith et al 2007;Agnoletto et al 2009). SLSNe without the signatures of interaction with a Hrich CSM, ("H-poor SLSNe") are in turn divided into two rather vaguely defined groups.…”
Section: Introductionmentioning
confidence: 99%